Influence of NaOH activator concentration on efflorescence and compressive strength of sustainable mortar with alkali-activated slag and fly ash binders - Osama A. Mohamed; Omar Najm; Shefin Shaji (International Journal of Sustainable Engineering, 2025)
The rapid expansion of global infrastructure has intensified the demand for sustainable alternatives to ordinary Portland cement (OPC). Alkali-activated binders using ground granulated blast furnace slag (GGBS) and fly ash have emerged as promising options due to their lower environmental footprint and enhanced performance. However, the combined effects of alkali activator concentration, binder composition, and curing conditions on mechanical strength and efflorescence remain insufficiently explored. This study addresses this gap by systematically examining the impact of varying sodium hydroxide (NaOH) molarities (6–12 mol/L) on mortar mixtures with different GGBS-to-fly ash ratios. Samples were cured either under water or in ambient conditions to evaluate the interplay between curing regime and activator concentration. Results show that water curing significantly improves strength development in GGBS-rich binders, while ambient curing promotes efflorescence, particularly at lower NaOH concentrations. An optimal NaOH concentration of 10 mol/L produced the highest 28-day compressive strength in mortars containing 75% or 100% GGBS. In contrast, fly ash-rich mortars performed better under ambient curing, suggesting that curing effects are composition dependent. This study provides new insights into optimising parameters that influence both mechanical and durability performance of alkali-activated mortars, offering practical guidance for sustainable binder design under diverse field conditions.